Spotlight — Management of pyelovesical bypass device stones - Almarzouq, Ahmad; Andonian, Sero (Canadian Urological Association Journal, 2018)
Pyelovesical bypass devices or artificial ureters have been described as a last resort in patients with long ureteral strictures that fail traditional endoscopic and open repair. Herein, we describe a 52-year-old female who had a Detour (Coloplast, Humlebaek, Denmark) pyelovesical bypass device inserted after an iatrogenic ischemic injury to the distal two-thirds of the left ureter during pelvic surgery for recurrent endometrial stromal sarcoma. Six months after placement of the device, she presented with gross hematuria and recurrent urinary tract infections (UTIs) and was found to have encrustation of the distal silicone tip of the Detour device within the bladder. This was managed with resection of the distal silicone tip and flexible ureteroscopy with holmium laser lithotripsy. Despite suppressive antibiotic therapy and medical therapy for hypercalciuria, she presented four years later with intraluminal encrustations in the proximal end of the device. This was successfully managed with flexible ureteroscopy with holmium laser lithotripsy. Therefore, this case illustrates the feasibility of flexible ureteroscopy and holmium laser lithotripsy of Detour device encrustations as long as the device is not kinked and it allows the passage of the flexible ureteroscope up to the calcifications. In addition, patients contemplating insertion of such devices should be counselled regarding the risk of recurrent infections and encrustations.